Selecting a suitable method and conditions for drying galangal (Alpinia galanga L.) rhizomes and holy basil (Ocimum sanctum L.) leaves based on physical characteristics, bioactive contents and bioactivities - Chhom, Muyny; Chantarapanont, Walairut; Sukatta, Udomlak (Agriculture and Natural Resources, 2022)
Galangal (Alpinia galanga L.) rhizome and holy basil (Ocimum sanctum L.) leaves are common herbs used in Asian food. Drying can prolong the shelf life of these herbs; however, different drying methods and conditions can affect their nutritive value. This research investigated the suitability of three drying methods for drying galangal rhizomes and holy basil leaves—tray drying (T), vacuum drying (V) and microwave vacuum drying (MV)using three different temperature conditions for T and V (40○C, 50○C or 60○C) and three different power settings for MV (1,200 W, 1,800 W or 2,400 W). Each plant sample was dried until its moisture content was less than 8% dry weight and then was tested for physical characteristics, bioactive content and bioactivities. The results showed that tray drying galangal rhizomes at 60°C for 3.5 hr and vacuum drying holy basil leaves at 40°C for 6 hr produced less color change (9.58±0.07 and 7.18±0.10, respectively) compared to fresh samples, high contents of total phenolic content (8.63±0.02 and 20.08±0.11, respectively) and total flavonoid content (3.81±0.01 and 16.49±0.05, respectively) with high antioxidant activities and showed anti-diabetic activity (α-glucosidase inhibition). Drying could improve the antioxidant and anti-diabetic activity levels of the galangal rhizomes and holy basil leaves. There were relationships among the color, bioactive compounds and bioactivity levels of the dried galangal rhizomes and holy basil leaves. Therefore, tray drying at 60°C for 3.5 hr and vacuum drying at 40°C for 6 hr were recommended for drying galangal rhizomes and holy basil leaves.